2009
DOI: 10.1155/2009/638585
|View full text |Cite
|
Sign up to set email alerts
|

Does Routine Pain Assessment Result in Better Care?

Abstract: The findings do not support the idea that the availability of systematic pain assessment information leads to change in clinician's medication practices. As such, educational interventions and public policy initiatives are needed to ensure that treatment providers do not only gather but also use pain assessment information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Two patients—1 female (33) multiple sclerosis; 1 male (58) severe multiple traumaQuantitative descriptivedos Santos Silva et al [42]BrazilNon-randomised controlled trial; patients’ medical reportsTo test the hypothesis that training for nurses of applying a systematised pain assessment of pain control effects decision-making regarding administration of morphine and affects pain relief for patientsNumeric Pain Rating Scale—pain levelCardiac Surgery. n  = 182 Cardiac surgery patients; mean age—55.7Correlation of variables—Chi-square, Likelihood Ratio Test; Descriptive statistics; Comparison among groups—Kruskal–Wallis and Dunn testHadjistavropoulos et al [44]CanadaNon-randomised controlled trial; patient-reported outcome measuresTo assess whether systematic pain assessment changes the clinical practice of medical practitioners21-point box scale*—pain levels, Geriatric Pain Measure (GPM)*—pain intensity, Geriatric Depression Scale (GDS-SF)*—depressionGeneral Practice. n  = 114 seniors with complex medical problems; mean age–80.74T testsHvitfeldt et al [33]USA/SwedenMixed-method—qualitative description and cross-sectional analytic study (triangulation design); questionnaires; Semi-structured interviewsTo identify the properties of a patient-reported measurement system in two different contexts.Oswestry Disability Index*—low back pain disability, SF-36*—health-related quality of life, Musculoskeletal Outcomes and Data Evaluation and Management System (MODEMS)—unknown1 Spine Centre (USA); 2 Rheumatology Clinics (Sweden). n  = 88 clinical patients; n  = 18 healthcare providers (15 MDs, 2 physiotherapists, 2 nurse practitioners)Quantitative data—Fisher’s exact 2-tailed test; qualitative data—Content analysisKazis et al [39]USARandomised controlled trial; questionnaires, patients’ medical recordsTo investigate the value of health status information on clinical practice for patients with rheumatoid arthritis.Arthritis Impact Measurement Scales (AIMS)*—physical, social and emotional wellbeing, Modified Health Assessment Questionnaire (MHAQ)*—health statusArthritis Centres.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two patients—1 female (33) multiple sclerosis; 1 male (58) severe multiple traumaQuantitative descriptivedos Santos Silva et al [42]BrazilNon-randomised controlled trial; patients’ medical reportsTo test the hypothesis that training for nurses of applying a systematised pain assessment of pain control effects decision-making regarding administration of morphine and affects pain relief for patientsNumeric Pain Rating Scale—pain levelCardiac Surgery. n  = 182 Cardiac surgery patients; mean age—55.7Correlation of variables—Chi-square, Likelihood Ratio Test; Descriptive statistics; Comparison among groups—Kruskal–Wallis and Dunn testHadjistavropoulos et al [44]CanadaNon-randomised controlled trial; patient-reported outcome measuresTo assess whether systematic pain assessment changes the clinical practice of medical practitioners21-point box scale*—pain levels, Geriatric Pain Measure (GPM)*—pain intensity, Geriatric Depression Scale (GDS-SF)*—depressionGeneral Practice. n  = 114 seniors with complex medical problems; mean age–80.74T testsHvitfeldt et al [33]USA/SwedenMixed-method—qualitative description and cross-sectional analytic study (triangulation design); questionnaires; Semi-structured interviewsTo identify the properties of a patient-reported measurement system in two different contexts.Oswestry Disability Index*—low back pain disability, SF-36*—health-related quality of life, Musculoskeletal Outcomes and Data Evaluation and Management System (MODEMS)—unknown1 Spine Centre (USA); 2 Rheumatology Clinics (Sweden). n  = 88 clinical patients; n  = 18 healthcare providers (15 MDs, 2 physiotherapists, 2 nurse practitioners)Quantitative data—Fisher’s exact 2-tailed test; qualitative data—Content analysisKazis et al [39]USARandomised controlled trial; questionnaires, patients’ medical recordsTo investigate the value of health status information on clinical practice for patients with rheumatoid arthritis.Arthritis Impact Measurement Scales (AIMS)*—physical, social and emotional wellbeing, Modified Health Assessment Questionnaire (MHAQ)*—health statusArthritis Centres.…”
Section: Resultsmentioning
confidence: 99%
“…Another study, which issued nurses with training on PROMs and implemented PROMs across a cardiac surgery ward, found that after training and implementation, patients had higher morphine consumption [42]. In comparison, three studies showed no significant differences in medication across intervention and control groups [39, 43, 44]. No significant differences were found in additional treatment [43], arthritis referrals [39], or reducing doctor visits [39].…”
Section: Resultsmentioning
confidence: 99%
“…Use of pain tools may improve pain treatment [179,180]. The Pain Assessment in Advanced Dementia (PAINAD), developed in the US, is a brief tool (5 items) for direct observation including by observers unfamiliar with the patient [131].…”
Section: Toolsmentioning
confidence: 99%
“…53 The literature indicates that the mere availability of systematic pain assessment data may not be sufficient to affect clinical decision making. 54 Furthermore, qualitative studies report that many clinicians wish to be involved in planning outcome assessment protocols. 55 This study purposefully sought input from a variety of pediatric pain clinicians to evaluate usefulness of the PQ and to determine the best route for future implementation.…”
Section: Discussionmentioning
confidence: 99%